2020
DOI: 10.1111/cpf.12658
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between trapezius muscle hardness and transverse cervical artery flow in association with neck and upper‐back stiffness

Abstract: Neck and upper-back stiffness is often encountered in daily life, even among healthy subjects. The symptom is also referred to as neck and shoulder stiffness, neck and shoulder pain, stiff shoulder,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, this study found no significant differences in the factors related to posture and physical activity, suggesting that differences in muscle hardness are not related to posture or physical activity. A previous study reported that the muscle hardness of the trapezius muscle is associated with blood flow velocity [38]. In addition to physical factors such as posture measured in this study, blood flow may have been related to muscle hardness.…”
Section: Discussionmentioning
confidence: 54%
“…However, this study found no significant differences in the factors related to posture and physical activity, suggesting that differences in muscle hardness are not related to posture or physical activity. A previous study reported that the muscle hardness of the trapezius muscle is associated with blood flow velocity [38]. In addition to physical factors such as posture measured in this study, blood flow may have been related to muscle hardness.…”
Section: Discussionmentioning
confidence: 54%
“…Muscle hardness was quantitatively evaluated by a trained examiner using a portable muscle hardness meter (NEUTONE TDM-Z2; TRY-ALL Corp., Chiba, Japan). A similar device was used in previous studies [ 22 24 ]. Our previous study showed that the muscle hardness meter had excellent intratester reliability for the trapezius muscle ( ICC 1,5 = 0.992–0.995) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another study evaluating the e cacy of muscle exercises in patients with neck pain [51] found that patients after lower trapezius strengthening exercises show signi cant improvement in muscle thickness and contraction, and these effects are positively correlated with the improvement of patients' neck pain symptoms. Many other studies [52,53] investigated the potential link between cervical muscle stiffness and neck pain. All these studies have proven the important role of cervical soft tissue in neck pain and cervical spine degeneration, as well as the stiffness of cervical soft tissue commonly associated with neck pain [54,55] .…”
Section: Cpstt and Neck Painmentioning
confidence: 99%